1994
DOI: 10.1007/bf00276475
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of specific wall proteins during yeast and mycelial protoplast regeneration in Candida albicans

Abstract: The kinectics of incorporation of two precursor mannoproteins into the regenerating cell wall of Candida albicans protoplasts have been followed at 28 degrees C and 37 degrees C using two monoclonal antibodies specific for protein epitopes (MAb 1B12 and 4C12) as probes. Both molecules were secreted from the beginning of the regeneration process, and their incorporation was retarded significantly. Analysis of the secreted materials by Western immunoblotting with MAb 1B12 allowed the identification of two closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
4
9
1
Order By: Relevance
“…Accordingly, it may be anticipated that during the process the cell must, on one side increase the expression of the genes necessary for recovery, and on the other hand maintain a balance in the expression of genes directly involved in wall formation, in order to build again its correct structure. According to the data here presented, the cell wall of C. albicans protoplasts grown in hypertonic liquid media, starts to be apparent after just 1 h of incubation, and its quasi normal structure is reached a few hours later, in agreement with our previous results (Elorza et al, 1994). Analytical determinations demonstrated that the initial Wbrillar material laid down by the protoplasts corresponded to chitin, whereas glucan and some mannoproteins were deposited later on (Elorza et al, 1987(Elorza et al, , 1994Murgui et al, 1986).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Accordingly, it may be anticipated that during the process the cell must, on one side increase the expression of the genes necessary for recovery, and on the other hand maintain a balance in the expression of genes directly involved in wall formation, in order to build again its correct structure. According to the data here presented, the cell wall of C. albicans protoplasts grown in hypertonic liquid media, starts to be apparent after just 1 h of incubation, and its quasi normal structure is reached a few hours later, in agreement with our previous results (Elorza et al, 1994). Analytical determinations demonstrated that the initial Wbrillar material laid down by the protoplasts corresponded to chitin, whereas glucan and some mannoproteins were deposited later on (Elorza et al, 1987(Elorza et al, , 1994Murgui et al, 1986).…”
Section: Discussionsupporting
confidence: 89%
“…The protoplasts of C. albicans are devoid of wall (Miragall et al, 1988) and regeneration is initiated by deposition of chitin followed by laying of glucan molecules that complement a network allowing incorporation of mannoproteins by covalent bonds (Miragall et al, 1986;Elorza et al, 1987). Interestingly enough, the nature of the protein complexes initially released by -glucases are diVerent from those extracted from growing cells (Elorza et al, 1994;Murgui et al, 1986). Our rationale was that a kinetic analysis of the transcriptional regulation occurring during the formation of a whole new cell wall by protoplasts would provide new insides on the building of the whole structure.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, in hypertonic liquid medium they synthesize b-1,3-glucans, chitin and a number of cell wall proteins, that form a loosely-bound coat surrounding the protoplasts and that may trap several protoplasts together, but do not organize into a normal cell wall (Svoboda et al, 2001). These results contrast with Candida albicans protoplasts that synthesize a rather normal cell wall when incubated in hypertonic liquid medium (Elorza et al, 1994;Sanjuan et al, 1996). The reasons for this different behaviour are not known, but it is likely that the difference must depend on some key processes involved in the organization of the structure of the wall.…”
Section: Introductioncontrasting
confidence: 60%
“…An important difference observed in the process occurring in both organisms was that the number of up-regulated genes related to cell wall synthesis and structure, and their corresponding expression, values that were significantly higher in C. albicans (Castillo et al, 2006). Also a noticeable difference was the observation that the up-regulated C. albicans genes involved in cell wall synthesis and structure increased their expression at different periods, and normally decayed (Castillo et al, 2006), following approximately the kinetics of the deposition of the corresponding polymers in the growing wall (see Elorza et al, 1987Elorza et al, , 1994Murgui et al, 1986). In contrast, up-regulated genes during regeneration of S. cerevisiae protop- lasts reached their highest values almost simultaneously after 2 h of incubation.…”
Section: Discussionmentioning
confidence: 93%
“…Beyond encouraging chemical and/or enzymatic approaches for its extraction from intact cells or isolated walls (22)(23)(24)(25) and bypassing their inherent troubles (glucan and/or chitin sidechain residues and protein modifications (19,26)), an innovative stratagem, based on the analysis of proteins secreted from protoplasts in active cell wall regeneration, has also recently enabled this Achilles' heel to be successfully profiled (26 -28). This modus operandi draws on the observation that these wall biogenesis-related proteins are not retained into the nascent cell wall during the early stages of the regeneration process and are thus shed into the extracellular medium (26,29).…”
Section: Not Only Does Systemic Candidiasis (Sc)mentioning
confidence: 99%